43. OVERVIEW OF THE PROFESSION HEALTH COACH: CURRENT STATUS, CHALLENGES, AND FUTURE PROSPECTS (Vietnam Journal of Community Medicine, 2025)
Objective: The rise in chronic diseases, sedentary lifestyles, and the growing demand for preventive healthcare have highlighted the role of health management and coaching. This study provides an overview of the current status of health management and coaching profession’s development, analyzes its role within healthcare systems, and identifies challenges and future opportunities.Methods: A literature review was conducted using reputable scientific databases such as PubMed, Scopus, and Google Scholar. Keywords including “health coaching”, “well-being”, “health management”, “chronic disease prevention”, “lifestyle intervention”, and “behavioral health coaching” were used to ensure a comprehensive scope of research.Results: Health management and coaching are increasingly recognized for their ability to support behavioral changes, improve chronic disease management, enhance treatment adherence, and promote mental well-being. However, the field faces challenges such as a lack of standardized training, insufficient integration into healthcare systems, and limited public awareness.Conclusion: Health coaching contributes to improved quality of life and plays a crucial role in proactive healthcare. To ensure sustainable development, further research, legal recognition, and integration into preventive healthcare programs are necessary.
Keywords: Health management; health coaching; proactive healthcare; challenges and opportunities